Non-insecticidal control of domestic and peri-domestic species of cockroach - Isaac Frimpong Aboagye; Andrew Nii Awuley Lartey; Festus Quainoo Anim; Maxwell Kelvin Billah (Journal of Basic and Applied Zoology)
Abstract Background Cockroaches transmit pathogens, including fungi, parasites, and bacteria, contaminating surfaces and materials in homes, underscoring the need for control. While insecticides are effective, they carry risks of exposure and adverse effects on humans and other organisms. This study tested safer, food-based alternatives using baking soda mixed with peanut butter and sugar as bait and assessed cockroach mortality counts in students’ bedroom, home kitchen, and storeroom settings. Results Blattella germanica and Periplaneta americana were trapped, with peanut butter and sugar attracting 578 and 326 cockroaches, respectively. Mortality was significantly higher with baking soda in peanut butter [χ2(1) = 41.39; p < 0.0001] and sugar [χ2(1) = 33.99; p < 0.0001] compared to controls in students’ bedroom. Comparable results were observed in the home kitchen and storeroom settings. The mean rank cockroach counts for peanut butter-baited and sugar-baited traps were 50.26 and 40.74, respectively (U = 798, p = 0.083). Conclusions These findings suggest that baking soda is an effective non-insecticidal agent for controlling populations of B. germanica and P. americana.